Prefrontal Abilities - D. F. Benson (Behavioural Neurology)
The neuroanatomical region that has most prominently altered with the advancing cognitive competency of the human is the prefrontal cortex, particularly the rostral extreme. While the prefrontal cortex does not appear to contain the neural networks that carry out cognitive activities, the management of these high level manipulations, so uniquely characteristic of the human, appears dependent upon the prefrontal cortex.